Pb-Contaminated Soil from Quintero-Ventanas, Chile: Remediation Using Sarcocornia neei - Meza-Ramírez, Verónica (ScientificWorldJournal, 2021)
A phytoremediation process for lead (Pb) under laboratory conditions on contaminated soil from the Puchuncaví commune, Valparaíso Province, Chile, was carried out. It analyzed the phytoremediation potential of Sarcocornia neei (Lag.) M.A. Alonso and M.B. Crespo. The plants were propagated beforehand and extracted from the El Yali wetland, a RAMSAR 878 site in Valparaíso. Soil fertility and heavy metal concentration analyses of composite samples were conducted, complying with established protocols and standard methodology for chemical and metal analyses. These analyses were conducted in the Soil Analysis Laboratory of the Pontificia Universidad Católica de Valparaíso. The aim was to analyse not only the tissue of plants from both areas but also the soil to identify the changes in different conditions in which the plants live. To determine the type of inferential analysis to be performed, a normality test was applied; however, it was deemed unsuitable, and therefore, the contrasts were developed using nonparametric tests, particularly Wilcoxon. R project software was used in the tests, especially the RCommander package, together with the Jamovi free-license statistical spreadsheet application. The analyses results of the soil samples indicated high concentrations of heavy metals, predominantly Pb at a concentration of 77.97 mg/kg, acidic soil indicated by pH between 5.77 and 6.38, low levels of electrical conductivity, and the presence of organic matter. A phytoremediation efficiency of 99% on soil samples was achieved. Preliminary results were compared against international regulations on the concentration of metals in soil. The histological sections showed that individual plants probably adapted to their environmental conditions.